Analysis of Machine Performance with Calculations Overall Equipment Effetiveness on Packing Line Automation Machine - Wiyatno, Tri Ngudi; Sutriyanto, Dwi; Edy, Sarwo; Sumarta, Sumarta (Formosa Journal of Sustainable Research, 2024)
This study continues the previous practical work, emphasizing the importance of machine maintenance, problem improvement, and production facility maintenance to maintain quality and productivity. The maintenance team aims to find the right system to reduce machine breakdowns and maintenance costs. Automation, such as the Automated Packing Line, was chosen to optimize production with minimal labor. This study analyzes the effectiveness of automation machines in the Packing Line area and evaluates the role of labor in continuous improvements to calculate Overall Equipment Effectiveness (OEE). Results show that the OEE of the traying machine in the Automated Packing Line is 79%, still below the standard of 85%. After improvements were made, the OEE value increased to 87%